2012 NASA/ESA Conference on Adaptive Hardware and Systems (AHS) 2012
DOI: 10.1109/ahs.2012.6268655
|View full text |Cite
|
Sign up to set email alerts
|

Cocoon-PUF, a novel mechatronic secure element technology

Abstract: A new Physical Unclonable Function (PUF) technology is proposed. The technology is targeting the implementation of a highly secure unclonable electromechanical device. The resulting system includes a physical unit providing identi¬fication properties mutually-dependent on both microelectronic and mechanical components. The tech¬nology is based on combining very high frequency wave propagation, scattering and reflection based on dielectric and/or magnetic particles or composites (potted) in matrices of a closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There has been some research on monitoring the HSM's interior using e.g. electromagnetic radiation [TZP,KA12] or ultrasound [Vri] but none of this research has found widespread adoption yet.…”
Section: Related Workmentioning
confidence: 99%
“…There has been some research on monitoring the HSM's interior using e.g. electromagnetic radiation [TZP,KA12] or ultrasound [Vri] but none of this research has found widespread adoption yet.…”
Section: Related Workmentioning
confidence: 99%
“…This paper is aimed at developing a new RF fingerprinting technology that is capable of producing and using PUFs as a new cryptographic-primitive [10]- [12]. This approach is based on advanced micro and nano materials in combination with microwave technology.…”
Section: Introductionmentioning
confidence: 99%